2002
DOI: 10.1007/s004420100791
|View full text |Cite
|
Sign up to set email alerts
|

Morphological plasticity of white clover (Trifolium repens L.) in response to spatial and temporal resource heterogeneity

Abstract: Heterogeneity in resource distribution has been an important selective force shaping morphological plasticity in plants. When resources are patchily distributed, changes in morphology are assumed to affect placement of the resource-acquiring structures (roots and leaves) such that they enhance the plant's capacity for resource uptake. Morphological development of four white clover (Trifolium repens) genets was studied in two glasshouse experiments. In the spatial experiment, two substrates (potting soil and sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 45 publications
(44 reference statements)
1
16
0
Order By: Relevance
“…This was consistent with the findings in Fragaria orientalis growing under a heterogeneous water supply (Zhang et al 2008). Many studies have reported that the morphological plasticity of clonal plants may facilitate exploitation of favorable rooting sites in heterogeneous microhabitats and so increase the efficiency of foraging for the resources they need (Birch and Hutchings 1994;Stuefer et al 1996;Hutchings 1996, 1999;Welham et al 2002;Day et al 2003;Roiloa and Retuerto 2006c). Under severe parental water stress, the remarkably smaller reduction in biomass of offspring ramets (34%) compared to that of parents (87%; Fig.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This was consistent with the findings in Fragaria orientalis growing under a heterogeneous water supply (Zhang et al 2008). Many studies have reported that the morphological plasticity of clonal plants may facilitate exploitation of favorable rooting sites in heterogeneous microhabitats and so increase the efficiency of foraging for the resources they need (Birch and Hutchings 1994;Stuefer et al 1996;Hutchings 1996, 1999;Welham et al 2002;Day et al 2003;Roiloa and Retuerto 2006c). Under severe parental water stress, the remarkably smaller reduction in biomass of offspring ramets (34%) compared to that of parents (87%; Fig.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, vegetative multiplication allows clonal plants to spread extensively and establish ramets in new microhabitats Retuerto 2006b, 2007). Many studies have shown that the morphological and physiological plasticity of clonal plants enable them to capture light and nutrients more efficiently (Birch and Hutchings 1994;Stuefer et al 1996;Wijesinghe and Hutchings 1999;Welham et al 2002;Day et al 2003;Roiloa and Retuerto 2006a, c). However, very few studies have looked at the effects of variable water availability on the morphology and physiology of clonal plants (Alpert and Mooney 1986;de Kroon et al 1996de Kroon et al , 1998Zhang et al 2003;Liu et al 2007;Savini et al 2008;Zhang et al 2008Zhang et al , 2009, especially in terms of gas exchange and osmotic regulation.…”
Section: Introductionmentioning
confidence: 98%
“…In general, resources are considered to freely translocate between ramets within a clonal plant through physical underground connections, usually from ramets on nutrientrich soil to ones within the same genet on nutrient-poor soil (Birch and Hutchings 1994;Stuefer et al 1996;Alpert and Stuefer 1997;Wijesinghe and Hutchings 1997;Van Kleunen and Stuefer 1999;Welham et al 2002;Yu and Dong 2003;Zang et al 2006). However, little attention has been paid to the duration of translocation between ramets.…”
Section: Discussionmentioning
confidence: 99%
“…The two most important environmental factors affecting the spatial distribution of ramets and their growth strategy are competition and distribution of resources (Hutchings and Mogie 1990). Gradients of environmental factors such as light (Solangaarachchi and Harper 1987;Weijschede et al 2006), density (Cain et al 1995), and substrate (Welham et al 2002) can induce a plastic response in Trifolium. Resources and competitors are often patchily distributed.…”
Section: Discussionmentioning
confidence: 99%